Diverse chirped optical solitons and new complex traveling waves in nonlinear optical fibers - Nestor, Savaissou; Abbagari, Souleymanou; Houwe, Alphonse; İnç, Mustafa; Betchewe, Gambo; Doka, Serge Y. (Iop Publishing Ltd, 2020)
This paper studies chirped optical solitons in nonlinear optical fibers. However, we obtain diverse soliton solutions and new chirped bright and dark solitons, trigonometric function solutions and rational solutions by adopting two formal integration methods. The obtained results take into account the different conditions set on the parameters of the nonlinear ordinary differential equation of the new extended direct algebraic equation method. These results are more general compared to Hadi et al (2018 Optik 172 545-53) and Yakada et al (2019 Optik 197 163108).
Keywords: diverse chirped optical solitons; nonlinear optical fibers; new extended direct algebraic method